What is Imagination? Perspectives Held by New Entrants into a B.Ed. Program - Hatt, Blaine E.; Graham, Rob (Alberta Journal of Educational Research, 2018)
This paper examines the preconceived notions and prior educational experiences that students entering a Bachelor of Education program have regarding imagination. Prior to the commencement of any course work, students (N=138) were asked in a survey to respond to two questions: “What is imagination?” and “Why do you hold that view?” The findings of this research project revealed that many students held traditional perceptions of imagination, such as the formation of a mental image or a concept of that which is not real or present, and the ability to deal creatively with reality. Students reported that their assumptions were based on ideas communicated to them by older siblings, parents, or primary elementary teachers. The evidence of traditional mindsets respecting imagination held by students entering a Bachelor of Education program calls for a deeper exploration of and conversation about the role of imagination in public education, especially in what some perceive to be a technologically advancing learning landscape requiring the essential 21st century competencies of critical thinking and creativity. Keywords: Imagination; Hume-Vygotsky principles: aesthetic/emotion, cognitive/experience, artistic/reality; Imagination Creativity Education (ICE) Cet article porte sur les notions préconçues et les expériences éducatives antérieures relatives à l’imagination d’étudiants au baccalauréat en éducation. Avant de commencer les travaux de leur programme, les étudiants (N=138) ont répondu à deux questions d’un sondage : « Qu’est-ce l’imagination? » et « Pourquoi êtes-vous de cet avis? ». Les résultats de ce projet de recherche révèlent que plusieurs étudiants entretenaient des perceptions traditionnelles de l’imagination, telles que la formation d’une image ou d’un concept mental qui n’est pas réel ou présent, ou bien la capacité d’affronter la réalité de façon créative. Les étudiants ont indiqué que leurs avis étaient basés sur des idées que leur avaient transmises leurs sœurs et leurs frères ainés, leurs parents ou leurs enseignants au primaire. Face à cette mentalité traditionnelle chez des étudiants qui débutent un baccalauréat en éducation, il serait nécessaire d’étudier en profondeur le rôle de l’imagination dans l’éducation publique et d’en discuter, notamment dans le contexte de ce que certains perçoivent comme étant un paysage d’apprentissage caractérisé par des progrès technologiques qui exigent les compétences essentielles du 21e siècle, soit la pensée critique et la créativité. Mots clés : imagination; principes Hume-Vygotsky : esthétique/émotion, cognitif/expérience, artistique/réalité; Imagination Creativity Education (ICE)